Short Segment Conduction Study and Localization Features in Ulnar Neuropathy at the Elbow: A Retrospective Study of 57 Patients - GÜNDÜZ, OSMAN HAKAN (BAYCINAR MEDICAL PUBL-BAYCINAR TIBBI YAYINCILIK, 2015)
Objective: The aim of this study was to investigate the localization properties in electrodiagnostically evaluated patients with a prediagnosis of ulnar neuropathy at the elbow. Material and Methods: The results of 57 patients who were electrodiagnostically defined as ulnar neuropathy at the elbow, with using short segment conduction study (SSCS), were evaluated retrospectively. The number of extremities determined as having focal conduction block with changes in latency was 30, while focal conduction alone was 27. The locations of nerve entrapment sites were determined as humeroulnar arcade (HUA), retroepicondylar groove (RTC), medial intermuscular septum (MIS). Results: The entrapment was found in the left upper extremity with a rate of 73%. The frequencies of localizations were determined for RTC (35%), MIS (25%), RTC+MIS (19%), HUA (16%), HUA+RTC (5%). Conclusion: The entrapments at RTC, MIS and HUA regions could be determined in patients whom 10 cm SCSS technique was used. The localizations of ulnar nerve entrapment at the elbow were RTC, MIS and HUA, in the order of decreasing frequency.
Keywords: Ulnar neuropathy; short segment conduction study; elbow; cubital tunnel syndrome; entrapment neuropathies; electromyography; CUBITAL TUNNEL-SYNDROME; ENTRAPMENT NEUROPATHY; NERVE-CONDUCTION; DIAGNOSIS; ELECTRODIAGNOSIS; MANAGEMENT; STRUTHERS; ARCADE